Monitoring Hatchlings in Aroen Meubanja, Aceh Jaya in Establishing Coastal Area Management - Heriansyah Heriansyah; Neneng Marlian; Friyuanita Lubis (Universitas Teuku Umar, 2022)
Sea turtles be found around Aroen Meubanja, Aceh Jaya at certain times of the year in raising their eggs in the coastal area. The aim of the research was to detect a collection of turtle eggs and be able to maintain their development until they hatch into hatchlings. This research was conducted in August – September 2019. The results of this study indicate that turtle conservation management in Aceh Jaya includes protecting turtles from their eggs until they are released to the beach in the afternoon. Turtle eggs are maintained by making nests with a width of 25 cm and a depth of 80 cm from the surface of the sand until they hatch into hatchlings. The community will release hatchlings into marine habitats and provide education through monitoring of coastal areas